An online gait generator for quadruped walking using motor primitives. (18th November 2016) - Zhou, Chunlin; Wang, Boxing; Zhu, Qiuguo; Wu, Jun
This article presents implementation of an online gait generator on a quadruped robot. Firstly, the design of a quadruped robot is presented. The robot contains four leg modules each of which is constructed by a 2 degrees of freedom (2-DOF) five-bar parallel linkage mechanism. Together with other two rotational DOF, the leg module is able to perform 4-DOF movement. The parallel mechanism of the robot allows all the servos attached on the body frame, so that the leg mass is decreased and motor load can be balanced. Secondly, an online gait generator based on dynamic movement primitives for the walking control is presented. Dynamic movement primitives provide an approach to generate periodic trajectories and they can be modulated in real time, which makes the online adjustment of walking gaits possible. This gait controller is tested by the quadruped robot in regulating walking speed, switching between forwardmovements and steering. The controller is easy to apply, expand and is quite effective on phase coordination and online trajectory modulation. Results of simulated experiments are presented.